Rheological Behavior of Tomato Fiber Suspensions Produced by High Shear and High Pressure Homogenization and Their Application in Tomato Products - Yong Wang; Ping Sun; He Li; Benu P. Adhikari; Dong Li (International Journal of Analytical Chemistry)
This study investigated the effects of high shear and high pressure homogenization on the rheological properties (steady shear viscosity, storage and loss modulus, and deformation) and homogeneity in tomato fiber suspensions. The tomato fiber suspensions at different concentrations (0.1%–1%, w/w) were subjected to high shear and high pressure homogenization and the morphology (distribution of fiber particles), rheological properties, and color parameters of the homogenized suspensions were measured. The homogenized suspensions were significantly more uniform compared to unhomogenized suspension. The homogenized suspensions were found to better resist the deformation caused by external stress (creep behavior). The apparent viscosity and storage and loss modulus of homogenized tomato fiber suspension are comparable with those of commercial tomato ketchup even at the fiber concentration as low as 0.5% (w/w), implying the possibility of using tomato fiber as thickener. The model tomato sauce produced using tomato fiber showed desirable consistency and color. These results indicate that the application of tomato fiber in tomato-based food products would be desirable and beneficial.